2002
DOI: 10.1093/hmg/11.8.945
|View full text |Cite
|
Sign up to set email alerts
|

Targeted disruption of Huntingtin-associated protein-1 (Hap1) results in postnatal death due to depressed feeding behavior

Abstract: HAP-1 is a huntingtin-associated protein that is enriched in the brain. To gain insight into the normal physiological role of HAP-1, mice were generated with homozygous disruption at the Hap1 locus. Loss of HAP-1 expression did not alter the gross brain expression levels of its interacting partners, huntingtin and p150glued. Newborn Hap1(-/-) animals are observed at the expected Mendelian frequency suggesting a non-essential role of HAP-1 during embryogenesis. Postnatally, Hap1(-/-) pups show decreased feeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 44 publications
4
54
0
Order By: Relevance
“…The highest P/S ratio of Hap1 was seen in the hypothalamus (Fig. 1B), in agreement with the finding that SBs are more abundant in the hypothalamus than in other tissues (5,10,14). Thus, these results showed that the use of a detergent-based strategy to enrich SBs in mouse brain was feasible.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The highest P/S ratio of Hap1 was seen in the hypothalamus (Fig. 1B), in agreement with the finding that SBs are more abundant in the hypothalamus than in other tissues (5,10,14). Thus, these results showed that the use of a detergent-based strategy to enrich SBs in mouse brain was feasible.…”
Section: Resultssupporting
confidence: 89%
“…DYRK1A is a major candidate gene for DS and likely is responsible for selective DS phenotypes. To look for DS symptoms that could be related to the regulation of DYRK1A on the Dcaf7-Hap1 interaction, we focused on growth retardation, which is a cardinal feature of DS (56) and is the most noticeable phenotype in Hap1-KO mice (5,10). Both individuals with DS and Hap1-KO mice exhibit impaired growth velocity after birth; the difference, however, is that in DS, growth velocity is most reduced between 6 mo and 3 y of age (56,57), whereas Hap1-KO mice are born at normal weight but display severe failure in body weight gain shortly after birth (5, 10).…”
Section: Discussionmentioning
confidence: 99%
“…Huntingtin-associated protein 1 (Hap1), originally identified as a neuronal protein that interacts with the Huntington disease (HD) protein, huntingtin (htt), is critical for postnatal development, as Hap1-KO mice often die before P3 due to inhibited feeding behavior (2,3). Mounting evidence has shown that both htt and Hap1 participate in intracellular trafficking of membrane receptors (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…HAP1 interacts with the type 1 inositol (1,4,5)-triphosphate receptor (IP 3 R1), forming an IP 3 R1-HAP1A-htt ternary complex in which mutant htt enhances the sensitivity of IP 3 R1 to IP 3 (Tang et al, 2003). In addition, the critical role of HAP1 for neuronal function has been demonstrated in HAP1 knock-out mice, which show a feeding defect and postnatal death (Chan et al, 2002;Dragatsis et al, 2004) possibly attributable to the selective degeneration of hypothalamic neurons (Li et al, 2003).…”
Section: Introductionmentioning
confidence: 99%